Dice and probabilities - Stankus , Eugenijus (Lietuvos matematikos rinkinys, 2009)
From the very birth of probability theory, the dice is one of the main means used to demonstrate the concepts of probability theory. In this article the illustration of various concepts of probability theory by experiments of rolling the dice is being investigated.
Keywords: dependence of events; dice, event; probabilit,; random variable